2013
DOI: 10.1021/jp4029408
|View full text |Cite
|
Sign up to set email alerts
|

Optical Probe of Charge Separation at Organic/Inorganic Semiconductor Interfaces

Abstract: Organic/inorganic semiconductor heterojunctions are being explored in hybrid solar cells that take advantage of unique properties of both material systems. A key question concerns the mechanism of charge separation across the localized/delocalized semiconductor interface. Here we probe photoinduced charge transfer at a model interface between copper phthalocyanine (CuPc) and gallium arsenide (GaAs) by tracking the electric field on the femtosecond time scale using timeresolved second harmonic generation. For a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…EFISH 22,23 is a fourwave mixing process: two optical fields at frequency o mix with a direct current field to give signal at frequency 2o. We have successfully implemented this in the time-resolved mode to detect transient electric fields resulting from charge separation at donor/ acceptor interfaces 21,[24][25][26][27] . The open circles in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EFISH 22,23 is a fourwave mixing process: two optical fields at frequency o mix with a direct current field to give signal at frequency 2o. We have successfully implemented this in the time-resolved mode to detect transient electric fields resulting from charge separation at donor/ acceptor interfaces 21,[24][25][26][27] . The open circles in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This process is also called electric-field induced SHG (EFISH) process. 13,15,48,[91][92][93][94][95][96][97][98][99][100][101] The former was excluded since the two surface states exhibit almost the same population rate in the early time upon the photoexcitation, as displayed in Fig. 5(c).…”
Section: Fig 4 Comparison Of Kinetic Profiles Of the Surface And Bumentioning
confidence: 99%
“…Recent studies showed that charge transfer occurs at semiconductor/organic thin film interfaces with timeresolved electric-field induced second harmonic generation (SHG), with the loss of spectral information. [13][14][15][16] Early efforts have also demonstrated the ultrafast relaxation of the surface photo-voltage (SPV) effect on semiconductors by timeresolved photoemission spectroscopy. [17][18][19] The time evolution of the electric field was demonstrated in the surface layer of semiconductors by measuring the kinetic-energy shifts of photoelectrons.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the difference transmission signal (Δ T / T ) is heavily suppressed by the absorption of surface excited carriers to cause the difficulties for the analyses. Comparing with the transmission configuration for the practical applications, the measurements of Δ R(ω )/ R(ω ) in the reflection configuration are more widely applied to various types of materials, including opaque materials, transparent materials9, bulk610, thin films11, and hetero-structures1213. Moreover, the ultra-broadband and 70-fs time-resolved spectra developed in this study are wide enough to provide more reliable fitting results and able to fully reveal the evolution of most of the features in spectra.…”
mentioning
confidence: 99%